Crisis and Change in the Japanese Financial System - Hoshi, Takeo; Patrick, Hugh T. (Springer US, 2000)
At the start of the twenty-first century, the Japanese financial system is undergoing a major transformation. This process is spurred by a sense of crisis. Dominated by large institutions, the Japanese banking system has suffered from serious problems with non-performing loans since the early 1990s, when the Japanese stock market and urban real estate market both crashed. Delays in responding to these twin asset bubbles, by both regulatory authorities and the banks themselves, made matters worse and led to a banking crisis in late 1997 and early 1998. Not anticipating this setback, in late 1996 the Japanese government inaugurated its Big Bang of comprehensive financial deregulation designed to complete the process of creating 'free, fair, and open financial markets'.
Keywords: Finance, general; International Economics; Macroeconomics/Monetary Economics//Financial Economics; Finance; International economics; Macroeconomics; Finanzpolitik; Finanzwirtschaft; Bankenkrise; Krise; Japan; Aufsatzsammlung